PERMAINAN TRADISIONAL KAULINAN BARUDAK UNTUK MENGEMBANGKAN SIKAP EMPATI DAN POLA GERAK DASAR ANAK USIA DINI - Nur, Lutfi; Halimah, Momoh; Nurzaman, Istikhoroh (Universitas Pendidikan Indonesia (UPI), 2017)
This research is based on the facts in the field regarding the process of achieving early childhood education that is not optimal. Eeducational attainment is about to manage sel emotion of early childhood. The traditional games